Prelabour Rupture of Membrane : Maternal and Foetal Outcomes - Jamal, Monira; Biswas, Rajat Kumar (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: The leading cause of perinatal morbidity and mortality is prematurity in developed and underdeveloped countries. In one third of the patients with preterm labour, there is associated premature rupture of membranes. The study was conducted to evaluate the clinical presentation of Pre-labour Rupture of Membrane (PROM) in pregnancy and obstetric outcome. Materials and methods: This is a cross sectional study carried out in the Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University, Dhaka, between September 2013 to February 2014. About 50 women having PROM with more than 32 weeks gestational age who admitted in the above department for delivery were enrolled in this study. Results: The mean age was found 27.4 ± 4.42 years with range from 17 to 41 years. Forty eight percent of PROM patient were primi and 52.0 percent of patients were multigravida. Six percent patients were illiterate. Almost two third patients were housewives. More than half (54.0%) of the patients were came from poor class income group family. Majority (64.0%) patients had term PROM (>37 weeks) gestational age and the mean gestational age was 38.1 ± 2.7 weeks with range from 32- 40 weeks. More than half (54.0%) didn't received any antenatal checkup. A total of (56.0%) patients had associated disease, out of which anaemia was more common. Twelve percent had diabetes mellitus and 8.0% had UTI infection. Almost two third (64.0%) was vaginal delivery and 18(36.0%) were caesarean section and common indication for caesarean section was fetal distress (38.9%). Two third patients were healthy and 17 patients had morbidities, wound infection is highest (29.4%). The mean birth weight was found 2.74 ± 0.7 kg. APGAR score >7 at 1 minute was found (92.0%) and (94.0%) at 5 minutes of birth of baby after birth. Fetal outcome take home alive (98.0%) and neonatal death 2.0%. Among 50 foetus morbidity develop in 26 cases. Among them respiratory insufficiency is highest (38.5%). Conclusion: Motivation of the patients, health education, improvement of nutritional status of mother, neonatal care service, early diagnosis, treatment, overall institutional delivery is needed for reduction of neonatal morbidity and mortality, as well as maternal morbidity. Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 23-27